Immune-targeted therapy with transarterial chemo(embolization) for unresectable HCC: a systematic review and meta-analysis - Fang, Huipeng; Ke, Qiao; Wu, Shiji; Tu, Qiang; Wang, Lei (Frontiers in Immunology, 2024)
Background: Transarterial chemo(embolization) is preferred for treating unresectable hepatocellular carcinoma (uHCC), questioned by the emerging immune-targeted therapies. This systematic review pioneers to evaluate the clinical efficacy and safety of transarterial chemo(embolization) combined with immune-targeted therapy for uHCC patients. Methods: PubMed, Embase, and Cochrane Library were searched for studies comparing immune-targeted therapy with or without transarterial chemo(embolization) until May 31, 2024. The complete response (CR) rate, objective response rate (ORR), and disease control rate (DCR) were considered to be the primary outcomes calculated for the clinical outcomes of transarterial chemo(embolization) combined with immune-targeted therapy, along with the progression-free survival (PFS) and overall survival (OS). The incidence of treatment-related severe adverse events was set as the major measure for the safety outcome. Results: Sixteen studies, encompassing 1789 patients receiving transarterial chemo(embolization) plus immune-targeted therapy and 1215 patients receiving immune-targeted therapy alone, were considered eligible. The combination of transarterial chemo(embolization) and immune-targeted therapy demonstrated enhanced outcomes in CR (OR=2.12, 95%CI=1.35-3.31), ORR (OR=2.78, 95%CI=2.15-3.61), DCR (OR=2.46, 95%CI=1.72-3.52), PFS (HR=0.59, 95%CI=0.50-0.70), and OS (HR=0.51, 95%CI=0.44-0.59), albeit accompanied by a surge in ALT (OR=2.17, 95%CI=1.28- 3.68) and AST (OR=2.28, 95%CI=1.42-3.65). The advantages of additional transarterial chemo(embolization) to immune-targeted therapy was also verified in subgroups of first-line treatment, intervention techniques, with or without extrahepatic metastasis, Child-pugh grade A or B, and with or without tumor thrombus. Conclusion: Combination of transarterial chemo(embolization) and immune-targeted therapy seems to bolster local control and long-term efficacy in uHCC, albeit at the expense of hepatic complications.